2017
DOI: 10.1212/wnl.0000000000004596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute intermittent hypoxia on hand use after spinal cord trauma

Abstract: NCT01272336.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…Furthermore, such results suggest uncovering how inflammation impacts the neural control of breathing is fundamental to understand changes in respiratory function during pathological conditions. Furthermore, for respiratory motor plasticity to be used clinically (21,45,46), we must also understand the interaction between plasticity and inflammation, which is common in many pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such results suggest uncovering how inflammation impacts the neural control of breathing is fundamental to understand changes in respiratory function during pathological conditions. Furthermore, for respiratory motor plasticity to be used clinically (21,45,46), we must also understand the interaction between plasticity and inflammation, which is common in many pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Complete or incomplete spinal cord injuries are characterized by spared synaptic pathways below the level of the injury. Intermittent hypoxia elicits plasticity in the spinal cord and strengthens these spared synaptic pathways, expressed as respiratory and somatic functional recovery in both experimental animals and humans with traumatic spinal cord injury (Navarrete-Opazo et al, 2015 , 2017a , b ; Dougherty et al, 2017 ; Trumbower et al, 2017 ). Table 5 lists studies reporting beneficial neurological impact after a wide range of intermittent hypoxia exposure protocols.…”
Section: Biological Effects Of Intermittent Hypoxia Exposurementioning
confidence: 99%
“…Recently, the use of repeated daily mild intermittent hypoxia has been endorsed as a stand-alone or adjunct therapy to promote the recovery of respiratory and limb motor dysfunction (Trumbower et al 2012, Tester et al 2014aNavarrete-Opazo et al 2017a,b;Trumbower et al 2017). Our results showed that exposure to mild forms of intermittent hypoxia increases loop gain and the arousal threshold that could lead to increases in apnoea frequency and duration in individuals with obstructive sleep apnoea.…”
Section: Translational Significancementioning
confidence: 48%
“…, b ; Trumbower et al . ). Our results showed that exposure to mild forms of intermittent hypoxia increases loop gain and the arousal threshold that could lead to increases in apnoea frequency and duration in individuals with obstructive sleep apnoea.…”
Section: Discussionmentioning
confidence: 97%